Climate Change Adaptation and Vulnerability Planning within the Municipal and Regional System: Examples from Northern Sweden - Larsson, Lars; Keskitalo, Carina; Åkermark, Jenny (Journal of Northern Studies, 2017)
The integration or mainstreaming of adaptation to climate change, while highly emphasized in the literature, is often operationally both very complex and places high requirements on resources for coordination in organizational units. This study reviews the development of integration of adaptation in the regional and local risk and vulnerability analysis processes, in the cases of the counties of Norrbotten and Västerbotten in Northern Sweden. The study concludes that adaptation as a non-binding and not specifically resourced policy area risks limited integration with existing measures. The Swedish distribution of authority and resourcing on adaptation, focusing on integrating adaptation within the municipal authority without specific funding, will thus constitute a limitation to integration and mainstreaming in particular in sparsely populated municipalities that despite limited tax bases are required to maintain the same municipal services as a larger municipality.